PENGARUH PEMBERIAN TANKOS DAN MIKORIZA TERHADAP PERTUMBUHAN DAN PRODUKSI SELADA (Lactuca sativa L.) - peru hermawan; Yunida Berliana; Triara Juniarsih (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2023)
This study aims to look at the effect of giving oil palm Tankos (empty fruit bunches) and mycorrhiza to the planting medium on the growth and production of lettuce (Lactuca sativa L,). The research was conducted in Medan Sunggal District, Medan City and was carried out from March 2022 to May 2022. The research method used was Factorial Randomized Block Design (RBD) with 2 treatment factors. The first factor was Tankos T0 (Control), T1 (100 gr/polybag), T2 (200 gr/polybag), T3 (300 gr/polybag). The second factor was Mycorrhiza M0 (Control), M1 (5 gr/polybag), M2 (10 gr/polybag). The results showed that the application of Tankos and Mycorrhizae showed a very significant effect on the parameters of Plant Height, Number of Leaves, Leaf Area, Dry Weight and Wet Weight of Lettuce Plants. The treatment Tankos T3 (dose =300 g/polybag) and Mycorrhiza M2 (dose =10 g/polybag) showed the highest results in all parameters. The interaction of the two treatments showed no significant effect, but it can be seen that the T3M2 treatment combination (tankos dose = 300 gr/polybag and mycorrhiza dose = 10 gr/polybag) was the best treatment in this study. It is suspected that the tankos is able to provide nutrients for the lettuce plants, while mycorrhiza helps the roots absorb the available nutrients for the lettuce plants.